2018
DOI: 10.1021/acs.analchem.8b04811
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented Reversible Real-Time Luminescent Sensing of H2S in the Gas Phase

Abstract: Hydrogen sulfide monitoring has become essential in the natural gas industry, biogas production, wastewater treatment plants, paper mills, sewers, and landfills of waste due to its toxic, irritating, extremely flammable, and corrosive features. However, each of the current monitoring technologies (gas chromatography, lead acetate tape, electrochemical, UV and NIR absorption) has its own limitations. Furthermore, the existing luminescent molecular probes for H 2 S cannot monitor it continuously due to the irrev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Luminescent europium and terbium complexes exhibit long-lived emissive peaks in the range of 490–700 nm, and europium ,, and terbium , probes based on copper precipitation have been reported. Luminescent iridium , and ruthenium , complexes have also been used to make hydrogen sulfide probes. Metal complexes such as these open up intriguing opportunities such as electrochemiluminescent sensing or reversible sensing using electron transfer reactions .…”
Section: Hydrogen Sulfidementioning
confidence: 99%
“…Luminescent europium and terbium complexes exhibit long-lived emissive peaks in the range of 490–700 nm, and europium ,, and terbium , probes based on copper precipitation have been reported. Luminescent iridium , and ruthenium , complexes have also been used to make hydrogen sulfide probes. Metal complexes such as these open up intriguing opportunities such as electrochemiluminescent sensing or reversible sensing using electron transfer reactions .…”
Section: Hydrogen Sulfidementioning
confidence: 99%
“…Kõrgmaa et al (2019) reported on the use of sensor‐based automation to improve sludge volume index in several water reclamation plants and process consistency. Urriza‐Arsuaga, Bedoya, and Orellana (2019) focused on improving the reliability of continuous monitoring technology for hydrogen sulfide which otherwise was difficult to achieve due to numerous constraints. A new sensor was developed and applied with favorable results.…”
Section: Instrumentationmentioning
confidence: 99%
“…Because dissolved CO 2 can reduce the solution pH, CO 2 sensors also employ pH indicators (colorimetric or fluorescent dyes) within various sensing layers such as silica gel coating, polymer matrix with quantum dots, and sol–gel matrix with silica nanoparticles [172,173,174,175,176,177]. H 2 S monitoring often utilizes reactive sensing materials such as Ag [178,179], Cu [180,181], ZnO [182,183], CuO doped SnO 2 [184], CdO [185], and fluorescent or luminescent indicators [186,187,188]. More H 2 S sensitive materials can be found in References [189,190].…”
Section: Emerging Corrosion Sensing Technologiesmentioning
confidence: 99%